1995
DOI: 10.1080/10407789508913746
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Coupled Turbulent Flow and Solidification for Steel Slab Casters

Abstract: A huo-dimenswnol -rim1modeling study was undertaken to account for coupled turbulent Jbw and hent transfer with solidijiurtrurtron in the mold and submold regr'ons of a steel slab caster. Liquid steel is inlmdued in& a waier-ewled mold through a bifiucated submerged entry Mule. Turbulence p h e m m e~ in the meU pool of the cactcr were accounted for, using a modified version of the low-Reymldr-number k-e turbulence model of Lounder and Sharma. nK mushy region solidificcrtion, in the presence of turbulence, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…13,14) The value of d is of the order of 1ϫ10 Ϫ4 m. The constant D 0 is assumed to be 1.8ϫ10 10 in this study. The constant q, introduced to avoid the division by zero, is set at 0.001.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14) The value of d is of the order of 1ϫ10 Ϫ4 m. The constant D 0 is assumed to be 1.8ϫ10 10 in this study. The constant q, introduced to avoid the division by zero, is set at 0.001.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Thus, it is very difficult to employ the wall functions. In this study, a revised version of low-Reynolds number k-e turbulence model by Launder and Sharma, 15) adopted by a few previous studies, 13,14) is used to consider the turbulent characteristics. A treatment for the release of latent heat in a mushy zone depends on a single-domain-based enthalpy method.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to account for the effect of the solid matrix on fluid flow in the mushy region, the enthalpy-porosity technique has been employed, wherein a source term, derived from Darcy's law of porous media, is incorporated in the momentum equation. 72,96) Many researchers model flow and solidification as a coupled problem on a fixed grid. [97][98][99] Although very flexible, this approach is subject to convergence difficulties and requires a fine grid to resolve the thin porous mushy zone next to the thin shell.…”
Section: Superheat Transfer and Solidificationmentioning
confidence: 99%
“…In fact, it has been emphasized that depending on the surface tension Reynolds number or Marangoni number (given by the ratio of surface tension gradient force to viscous force as Ma = (ρl ref,v is the characteristic length given by the viscous boundary layer thickness, the other terms are defined later), the transport in the molten pool may become turbulent in nature. As such, it has been observed that in case of surface tension-driven flows, the flow becomes turbulent if the surface tension Reynolds number is greater than 100 (Aboutalebi et al, 1995). It can be shown that typically for a high-power laser melting, the surface tension Reynolds number is much greater than 100.…”
Section: Introductionmentioning
confidence: 98%